The Rise of Reason in Planning Law: Daniel R. Mandelker and the Relationship of the Comprehensive Plan in Land Use Regulation - Edward J. Sullivan (Washington University Journal of Law & Policy, 2000)
This Essay focuses upon the skills of our honoree, Professor Daniel R. Mandelker, in presenting and advocating the fundamental organizing principles of planning law itself.
Keywords: City planning and redevelopment law; Land use